Comparison of Different Bone Filling Materials and Resorbable Membranes by Means of Micro-Tomography. A Preliminary Study in Rabbits - Fernández Bodereau, Enrique (2019)
Fil: Fernández Bodereau, Enrique. Universidad Nacional de Córdoba. Facultad de Odontología. Departamento de Prostodoncia; Argentina.